Clavate Tortoise Beetle, Plagiometriona clavata (Fabricius) (Insecta: Coleoptera: Chrysomelidae) - Robert E. Woodruff (EDIS)
Plagiometriona clavata (Fabricius) is common and can be recognized easily by its general form and appearance. Written for the Featured Creatures Collection by Robert E. Woodruff. Original publication date December 2006, revised August 2015. (Photo Credit: David Cappaert, www.forestryimages.org)